1985
DOI: 10.1207/s15327752jpa4903_16
|View full text |Cite
|
Sign up to set email alerts
|

Schizophrenic, Depressive, and Nonpatient Personality Organizations Described by Rorschach Factor Structures

Abstract: Rorschachs of 155 schizophrenics, 102 depressives, and 186 nonpatients were collected and scored using the Comprehensive System. Twenty-seven Rorschach variables considered central to interpretation were selected for study. Factor analyses and partial correlations controlling for number of responses, R, were generated in order to investigate the personality organization of each of the three groups. A three factor solution was found to be optimal for each group. Patterns of personality organization were discuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
27
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 1 publication
5
27
0
Order By: Relevance
“…These factors strikingly resemble factors that have been identified in prior factor analyses of adult Rorschachs using the CS (e.g., Fitzgerald, 1990Fitzgerald, / 1991Mason et al, 1985;Meyer, 1992;Zillmer & Perry, 1996;Zillmer & Vuz, 1995). Future researchers may wish to explore whether these same three factors can also be found in samples of preadolescent children.…”
Section: Three Factors Of the Comprehensive Systemsupporting
confidence: 64%
“…These factors strikingly resemble factors that have been identified in prior factor analyses of adult Rorschachs using the CS (e.g., Fitzgerald, 1990Fitzgerald, / 1991Mason et al, 1985;Meyer, 1992;Zillmer & Perry, 1996;Zillmer & Vuz, 1995). Future researchers may wish to explore whether these same three factors can also be found in samples of preadolescent children.…”
Section: Three Factors Of the Comprehensive Systemsupporting
confidence: 64%
“…Another possible interpretation for these results, not considered by Mason et al (1985), is that the variation of the factor structure by groups is part of a larger problem. It is possible that the test is unreliable and hence will always provide a different factor solution with any group.…”
mentioning
confidence: 96%
“…Although Mason et al (1985) found meaningful factors, their study is the only attempt thus far to factor analyze the Comprehensive System of the Rorschach. Mason et al used factor analysis as a way to identify the best group-test fit.…”
mentioning
confidence: 98%
See 2 more Smart Citations